Cell type and sex specific mitochondrial phenotypes in iPSC derived models of Alzheimer’s disease - Flannagan, Kaitlin; Stopperan, Julia A.; Hauger, Brittany M.; Troutwine, Benjamin R.; Lysaker, Colton R.; Strope, Taylor A.; Csikos Drummond, Vivien; Gilmore, Caleb A.; Swerdlow, Natalie A.; Draper, Julia M.; Gouvion, Cynthia M.; Vivian, Jay L.; et al. (Frontiers in Molecular Neuroscience, 2023)
Introduction: Mitochondrial dysfunction is observed in Alzheimer's disease (AD). Altered mitochondrial respiration, cytochrome oxidase (COX) Vmax, and mitophagy are observed in human subjects and animal models of AD. Models derived from induced pluripotent stem cells (iPSCs) may not recapitulate these phenotypes after reprogramming from differentiated adult cells. Methods: We examined mitochondrial function across iPSC derived models including cerebral organoids, forebrain neurons, and astrocytes. iPSCs were reprogrammed from fibroblasts either from the University of Kansas Alzheimer's Disease Research Center (KU ADRC) cohort or purchased from WiCell. A total of four non-demented and four sporadic AD iPSC lines were examined. Models were subjected to mitochondrial respiration analysis using Seahorse XF technology, spectrophotometric cytochrome oxidase (COX) Vmax assays, fluorescent assays to determine mitochondrial mass, mitochondrial membrane potential, calcium, mitochondrial dynamics, and mitophagy levels. AD pathological hallmarks were also measured. Results: iPSC derived neurons and cerebral organoids showed reduced COX Vmax in AD subjects with more profound defects in the female cohort. These results were not observed in astrocytes. iPSC derived neurons and astrocytes from AD subjects had reduced mitochondrial respiration parameters with increased glycolytic flux. iPSC derived neurons and astrocytes from AD subjects showed sex dependent effects on mitochondrial membrane potential, mitochondrial superoxide production, and mitochondrial calcium. iPSC derived neurons from AD subjects had reduced mitochondrial localization in lysosomes with sex dependent effects on mitochondrial mass, while iPSC derived astrocytes from female AD subjects had increased mitochondrial localization to lysosomes. Both iPSC derived neurons and astrocytes from AD subjects showed altered mitochondrial dynamics. iPSC derived neurons had increased secreted Aβ, and sex dependent effects on total APP protein expression. iPSC derived astrocytes showed sex dependent changes in GFAP expression in AD derived cells. Conclusions: Overall, iPSC derived models from AD subjects show mitochondrial phenotypes and AD pathological hallmarks in a cell type and sex dependent manner. These results highlight the importance of sex as a biological variable in cell culture studies.